THE EFFECT OF FINTECH USAGE ON CONSUMER BEHAVIORAL INTENTIONS THROUGH FINANCIAL LITERACY AND CUSTOMER SATISFACTION ON INVESTMENT APPLICATIONS - Ismawati; Agus Maolana Hidayat; Mahir Pradana (PT. Jurnal Center Indonesia Publisher, 2025)
This study seeks to explore the relationship between the understanding of fintech usage, behavioral intention, financial literacy, customer satisfaction, and brand image within the framework of the Bibit investment application. As consumer awareness of digital financial services continues to increase, companies are adopting strategies to strengthen user engagement and foster trust. The research highlights the critical role of financial literacy and customer satisfaction in cultivating stronger relationships between users and fintech platforms. The findings indicate that enhancing financial literacy and providing intuitive, user-friendly experiences not only elevate customer satisfaction but also encourage greater user loyalty. In light of the rising demand for informed decision-making and trust in digital financial services, fintech platforms that align with consumer expectations regarding education and service quality are better positioned to build long-term, meaningful relationships with users, thereby promoting sustained engagement and brand loyalty. Furthermore, the paper addresses the potential directions for future research focused on enhancing customer engagement with fintech platforms, particularly in the context of a highly competitive and awareness-driven market.